“Emedica: A Noninvasive Device to Improve Insulin Sensitivity in Type 2 Diabetes Patients”. - Hemant Rohera; Dr Ramesh Chouhan; Dr. Mrunali Jambhulkar; Dr. Vaishali Khatri; Dr. Deepak Nagpal (Revista Electronica de Veterinaria, 2024)
Insulin resistance is a key factor in the pathogenesis of type 2 diabetes mellitus (T2DM). This study is aimed to evaluate the effect of eMedica, a noninvasive device working on frequency-modulated electrical current therapy, in fat reduction and improved insulin sensitivity in type 2 diabetic patients. A cross-sectional study design was employed to evaluate alterations in insulin resistance, heart health, and the functioning of cells through statistical analysis in cohort of 25 patients with T2DM. The dataset provided insights into the glucose levels and insulin measurements of participants. The mean blood sugar level before and after intervention with eMedica therapy is 151.14 mg/dl, dropping significantly to 58.30 mg/Dl after therapy by e-Medica. These findings can help tailor diabetes management strategies and contribute to further analysis of participants’ health profiles and treatment responses. This drop in the blood sugar levels after using eMedica therapy is prominent finding which can be used in routine management of the patients.